O analista curador: um estudo sobre a escuta analítica - Piné, Alexandre de Souza (2012)
The present study sought to reflect on the goals that guide the analyst's listening in his clinical practice. Starting from the question posed by Lacan, "what am I authorized to do?" supplemented by the subsequent question, "what is the authorship of the analyst?" I have entered a path on the dimensions of aesthetics and justice, from the perspective of the healer. In the first, I find the priority notion of a sensitive knowledge, such as that uniting the analyst to the dimension of the unconscious happening. In the second, I realize that it is in the opposition to the role of the healer, that the analyst carries the symptomatic suffering issues to the court of unconscious choices. Analytical justice maintains ethics grounded on the fates that the subject offers to these choices. As from the narration of passages of a service, I build and calculate such notions into practice, and in the end I conclude that such goals, that of aesthetics and justice represent fields of expertise, whose stage is necessarily the analyst himself